“I became alright after birth”: Mechanisms driving improvements in mental health symptoms in the postpartum transition among persons at risk for HIV in South Africa - Katherine E. Kabel; Jane H. Lee; Jennifer N. Githaiga; Linda Gwangqa; Madison R. Fertig; Lauren R. Gulbicki; Maria J. Bustamante; Lucia Knight; Conall O’Cleirigh; Christina Psaros; Amelia M. Stanton (Women's Health)
Background: Pregnant and postpartum persons (PPPs) are at increased risk for HIV acquisition, and depression and posttraumatic stress disorder (PTSD) negatively impact engagement in HIV prevention behaviors like pre-exposure prophylaxis (PrEP) use, thereby increasing risk. Objectives: The present study explored changes in mental health symptoms from pregnancy to postpartum to inform future interventions for PPP that address mental health and HIV prevention. Design: This analysis is part of a larger, mixed-methods study conducted in South Africa that examined antenatal mental health barriers to PrEP use, employing an explanatory sequential design. Methods: Participants recruited from an antenatal clinic were pregnant or postpartum, over 18, not on PrEP, and with no history of PrEP use. Participants first took a survey to assess depression and PTSD symptoms. Those with elevated symptoms during pregnancy completed qualitative interviews during pregnancy and postpartum. Data were analyzed via thematic analysis. Results: Of 110 survey participants, 23 completed qualitative interviews (10 pregnancy only, 6 postpartum only, 7 both). This analysis includes 13 participants who completed either both interviews or postpartum only. Three themes illustrated processes linked to symptom reduction postpartum: (1) increased feelings of empowerment (e.g., via acceptance of life circumstances), (2) improvements in emotional and tangible support (e.g., via improved communication, increased caretaking and financial support), and (3) conceptualizations of infants and motherhood as sources of joy and motivation (e.g., pride in maternal role, companionship with baby). Conclusion: These themes highlight processes that may contribute to reductions in depression and PTSD symptoms postpartum, which could be integrated into interventions targeting mental health and HIV prevention during pregnancy. Intervention components may include skills promoting self-efficacy, problem-solving, communication, and identifying sources of joy and meaning. Interventions leveraging these mechanisms of symptom improvement during the postpartum transition may enhance mental health during pregnancy and promote greater engagement in HIV prevention behaviors.